Ergonomic Workstation Design of Metal Stamping Process to Improve Occupational Health in Malaysian Small and Medium Industries (SMIs) - Isa, Halim (2006)
Safe workstation design is considered as a vital contributor to feasible occupational health and it is believed to be one of effective approaches that can influence the productivity and competitiveness in almost companies under Malaysian Small and Medium Industries (SMIs). In Malaysian SMIs, metal stamping process is done using stamping machine and involved manual handling tasks such as feeding the raw material into machine die, transferring the finished products into container and others. These practices may lead to occupational diseases if the workstation of stamping process is not designed ergonomically. The objectives of the research are to propose the ergonomic workstation design for metal stamping process and evaluate the effectiveness of the proposed design. Ergonomic assessment using Rapid Entire Body Assessment (REBA) and surface Electromyography (sEMG) were applied to assess and analyze the working posture and muscle activity of workers while performing metal stamping process. From both assessments, the results have shown that ergonomic workstation design has improved working posture and reduced the exertion of work/loading on the muscles of the workers. The proposed design can be adopted to establish conducive working conditions of metal stamping process and thus improve the occupational health practices.